Prevalência e aspectos clínicos e epidemiológicos de mulheres HIV positivas infectadas pelo Papilomavírus humano (HPV) genital na Amazônia Brasileira - CHAGAS, Elcimara da Paixão Ferreira (Universidade Federal do Pará, 2017)
The Human Immunodeficiency Virus (HIV) has been shown to potentiate the oncogenic mechanisms of Genital Infection by the human papillomavirus (HPV) , it is believed that the state of immunocompetence of the host may play a role in the evolution of cervical lesions . HPV infects a large proportion of women worldwide , with an STD (sexually transmitted disease) more common in the world with approximately 291 million carriers of this virus women. This keeps information related to the annual incidence of nearly 500,000 cases of cervical cancer . According to the National Cancer Institute (INCA) , this is the second most frequent cancer in a Brazilian population and more common in Pará The objective is to detect the prevalence and clinical and epidemiological aspects of the HIV -infected women postivas HPV. It is cross - analytical study . The samples are from patients treated at the Counseling and Testing Center (ATC) of the municipality of Tucuruí from March 2011 to July 2013 for detection and enumeration of CD4 and CD8 T cells was performed the technique of nested- PCR , and qPCR , and the slides were stained by the Papanicolaou method. The prevalence of HPV was 68 % . Most were married / common-law marriage (63.5 %) , illiterate / incomplete primary (50 % ). Regarding gynecological history, 94.59 % used condoms in all relationships , the median age of first sexual intercourse was 13 years , and only 24.3 % had their first intercourse at age 14 or less . Among the respondents, 82.4 % had 2 or more sexual partners during their lifetime , with a median of 6 partners . HIV infection is considered a risk factor for development of cervical cancer and during the survey data showed that the CD4 + count is inversely proportional to the emergence of this disease were correlated . Eighty percent of the samples that were positive for HPV DNA were detectable after 9 subtypes (6, 11, 16 , 18, 31 , 33, 35 , 52, 58) studied, and 88% positive DNA HPV of the samples were subtyped with one or more subtypes high risk for cervical cancer . The population estimate of HIV positive women for the presence of HPV and its subtypes were of great importance to aid in the early diagnosis and treatment , provide subsidies to regionalized programs for the prevention and management of these infections.